Feeding behavior of the white-winged coot (Fulica leucoptera) along the middle Parana river inundation area, Argentina (2011)
The article describes the feeding behavior of the white-winged coot (Fulica leucoptera) by analyzing the stomach contents of 15 individuals with the stereoscopic microscope set to different degrees of taxonomic resolution: trophic spectrum was integrated by 14 taxonomical entities (4 vegetables and 10 animals); trophic diversity by stomach (H) oscillated between 0 and 1,95; accumulative trophic diversity (Hk) was 2,55; relative importance index (RII) values were Paspalum repens 253, Polygonum accuminatum 104, Belostoma 78, among others; trophic niche amplitude by season (estimated by using the Levins index) was 0,72 for summer, 0,46 for spring, 0,8 for fall and 0,86 for winter; prey percentages by size depicted 82% for organisms between 0 and 10 mm; an intestinal coefficient average (R) was 2,84. Based on those results, the author concludes that the Fulica leucoptera is an omnivorous species, mostly phytophagous.